Cu4sns4 Thin Films Fabricated by Sulfurizing Thermally Evaporated Cu/Sn/Cu Metal Layers - Radhalayam, D (Elsevier B.V., 2025)
Cu4SnS4 thin films show potential for photovoltaic applications due to their direct bandgap and high absorption coefficient. This study explores a two-step process for fabricating these films through thermal evaporation followed by sulfurization. Cu/Sn/Cu layers are deposited on Mo-coated glass substrates, and then sulfurized in a furnace at 550 °C for 10 to 60 min. Films sulfurized for 10 and 30 min exhibited large grain sizes, a highly crystalline structure, and uniform surface morphology, with bandgaps between 1.05–1.1 eV and electrical resistivity between 0.87 and 0.65 Ω cm, making them suitable for solar cells. However, sulfurization for 60 min caused a reduction in thickness and pinhole formation due to material loss. This method shows promise for producing high-quality Cu4SnS4 films for thin-film solar cells. © 2024